The infrared spectrum of [Ni(H2O)4][VOPO4]2 - Baran, Enrique José (1995)
While phosphato-vanadates, containing vanadium (V) have been extensively investigated [1, 2], similar phases with vanadium (IV) have received attention only recently [3-6]. These materials have a very rich and complex structural chemistry and present interesting intercalculation and catalytic properties [7-9]. Therefore, and with the aim to advance the general characterization of this type of compounds, we have initiated systematic studies of their vibrational properties [10-12]. In the present paper we report the results of an IR-spectroscopic study of [Ni(H2O)4][VOPO4]2.